Beyond negativity? A laboratory study on emotional responses to populist strategies on social media - Lindholm, Jenny; Eklund, Jesper; Strandberg, Kim; Carlson, Tom; Andersson, Sören (Frontiers in Political Science, 2024)
This exploratory laboratory study analyzes emotional responses to two types of populist strategies on social media platforms. We focus on emotional responses to content expressing ordinariness (on Instagram) and victimhood (on TikTok), where the content creator is a right-wing populist leader who is unfavorably perceived by the respondents in the study. Thus, the study critically tests the effectiveness of de-demonization strategies used by populist leaders to diversify the electorate. The research employs a combination of facial expressions analysis and two self-report measures of emotions to investigate the emotional responses elicited by populist strategies in individuals belonging to an out-group. Additionally, we examine the interrelation between psychophysiological measures and self-reported emotions. In doing so, the study makes a methodological contribution by advancing our understanding of emotional response processes and the methodologies employed to measure emotional responses. The results reveal positive and negative emotional responses, challenging the prevailing emphasis on negative emotions in response to out-group communication. However, the facial expressions and the self-reported emotions do not correlate. Our interpretation underscores the role of cognitive reasoning processes in differentiating emotional responses to political out-group social media content.